Oxygen, a Key Factor Regulating Cell Behavior during Neurogenesis and Cerebral Diseases - Zhang, Kuan; Zhu, Lingling; Fan, Ming (Frontiers in Molecular Neuroscience, 2011)
Oxygen is vital to maintain the normal functions of alomost all the organs, especially for brain which is one of the heaviest oxygen consumers in the body. The important roles of oxygen on the brain are not only reflected in the development, but also showed in the pathological processes of many cerebral diseases. In the current review, we summarized the oxygen levels in brain tissues tested by real-time measurements during the embryonic and adult neurogenesis, the cerebral diseases or in the hyperbaric/hypobaric oxygen environment. Oxygen concentration is low in fetal brain (0.01%- 1%) and in adult brain (1.5%-7%), decreased during stroke, and increased in hyperbaric oxygen environment. In addition, we reviewed the effects of oxygen tensions on the behaviors of neural stem cells (NSCs) in vitro cultures at different oxygen concentration (2%-20%) and in vivo niche during different pathological states and in hyperbaric/hypobaric oxygen environment. Moderate hypoxia (3%-10%) is known can promote the proliferation of NSCs and enhance the differentiation of NSCs into the TH-positive neurons. Next, we briefly presented the oxygen-sensitive molecular mechanisms regulating NSCs proliferation and differentiation recently found including the Notch, BMP and Wnt pathways. Finally, the future perspectives about the roles of oxygen on brain and NSCs were given.